PENGARUH ANALISIS LAPORAN KEUANGAN TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI: STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR LOGAM DASAR BESI DAN BAJA YANG TERDAFTAR DIBURSA EFEK INDONESIA - Winda Hutabarat; Ananta Sitorus; Samuel Hutabarat; Hamonangan Siallagan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of financial statement analysis on investment decision making in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses secondary data in the form of financial statements of manufacturing companies listed on the IDX during the 2019-2021 period. And of the eight iron and steel base metal subsector companies listed on the IDX, PT Betonjaya Manungal Tbk, PT Liomesh Prima Tbk, and PT Saranacentral Bajaratma have the highest final scoring level than the other averages and are companies that are worthy of investment media, which means that the company has a good level of future cash flow and low risk. Data analysis was conducted using multiple linear regression. The results showed that financial statement analysis has a positive and significant influence on investment decision making. This finding indicates that investors use the information contained in financial statements to assess company performance and make rational investment decisions. This research contributes to investors, company management, and capital market regulators in understanding the importance of financial statement analysis in making investment decision.